Hydroisomerization of Long‐Chain n‐Alkanes over Bifunctional Zeolites with 10‐Membered‐ and 12‐Membered‐Ring Pores1. Issue 1 (11th December 2017) - Zschiesche, Christopher; Himsl, Dieter; Rakoczy, Rainer; Reitzmann, Andreas; Freiding, Jens; Wilde, Nicole; Gläser, Roger
Abstract: The hydroisomerization of a C10 –C13 n ‐alkane mixture was investigated over six bifunctional platinum‐containing zeolite catalysts with 10‐ and 12‐membered‐ring pore systems. The catalysts with 12‐membered‐ring zeolites are more active than those with 10‐membered‐ring zeolites. In contrast, higher yields of the desired monobranched isomers are obtained over the 10‐membered‐ring zeolites due to shape‐selectivity effects. For the 10‐membered‐ring zeolites, higher reaction temperatures are required for achieving the maximum isomer yields, which leads to more cracking products compared to the 12‐membered‐ring zeolites. Abstract : Shape‐selective properties of bifunctional Pt‐containing zeolite catalysts were exploited for hydroisomerization of a long‐chain C10 –C13 n ‐alkane mixture. Zeolite catalysts with 12‐membered‐ring pore systems show a higher activity than with 10‐membered‐ring pore systems. Higher yields of the desired monobranched isomers are achieved over the 10‐membered‐ring zeolites due to shape‐selectivity effects.